2023
DOI: 10.1111/acer.15008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological administration of 3α,5α‐THP into the nucleus accumbens core increases 3α,5α‐THP expression and reduces alcohol self‐administration

Abstract: Background: Alcohol affects multiple circuits in the brain, mainly disrupting the delicate balance between inhibitory γ-aminobutyric acid (GABA) transmission and excitatory glutamate signaling in brain areas involved in reward circuits. These include the amygdala, nucleus accumbens (Acb), and ventral tegmental area (VTA). This action impairs circuits that regulate behavioral control of craving and alcohol seeking and intake. Studies in both rodent models and postmortem human brain of patients with alcohol use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Indeed, the efficacy of 3α,5α-THP administration to reduce cocaine reinstatement was observed in cocaine-dependent animals [ 48 , 49 ], and female rats were more sensitive to this effect [ 50 , 51 ]. Other findings showed that pregnenolone and its GABAergic metabolites regulate alcohol motivation by reducing alcohol seeking and intake in rodents [ 52 , 53 , 54 ]. These results were confirmed in clinical studies in patients with history of cocaine and alcohol use disorders [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the efficacy of 3α,5α-THP administration to reduce cocaine reinstatement was observed in cocaine-dependent animals [ 48 , 49 ], and female rats were more sensitive to this effect [ 50 , 51 ]. Other findings showed that pregnenolone and its GABAergic metabolites regulate alcohol motivation by reducing alcohol seeking and intake in rodents [ 52 , 53 , 54 ]. These results were confirmed in clinical studies in patients with history of cocaine and alcohol use disorders [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies in alcohol-preferring P rats by O'Dell et al (2005) [395] and Besheer et al (2010) [48] demonstrate that systemic administration of pregnenolone, epiallopregnanolone (3β,5β-THP), or the synthetic neurosteroid 3α,5β-20-oxo-pregnane-3-carboxylic acid (3α,5β-PC) reduces ethanol self-administration. Furthermore, Ornelas et al (2023) [50] found that infusion of allopregnanolone in the nucleus accumbens decreases alcohol self-administration in female P rats.…”
Section: Substance Use Disordersmentioning
confidence: 99%